Distributed regular polygon formation control and obstacle avoidance for non‐holonomic wheeled mobile robots with directed communication topology. Issue 9 (6th April 2020) - Wang, Zhuping; Wang, Lei; Zhang, Hao; Chen, Qijun; Liu, Jingcheng
Abstract : This study investigates distributed regular polygon formation control and obstacle avoidance problem for multi‐robot systems with the leader–follower structure. The communication topology of the networked multi‐robot system is modelled by a directed graph. Firstly, a distributed state observer is designed such that only part of the follower robots need to know the desired distance between the leader and followers. Based on the state observer, distributed obstacle avoidance can be realised. Then, an improved state transformation is designed such that the formation control of multiple non‐holonomic wheeled mobile robots with observed states can be converted into a consensus‐like problem. Based on the state transformation, novel controllers are proposed to achieve the formation control objectives. Finally, the effectiveness of the proposed control laws is verified by simulations.